A meta-analysis of eWallet adoption using the UTAUT model - Bommer, William H; Rana, Shailesh; Milevoj, Emil (International journal of bank marketing, 2022)
PurposeThis study aims to integrate extant research on eWallet adoption to better understand the key antecedents to eWallet use intention and examine whether the relationships differ across multiple moderators.Design/methodology/approachTo integrate eWallet adoption findings, the unified theory of acceptance and use of technology (UTAUT) and its extensions were utilized. Meta-analyses estimated the relationships between eWallet use intention and seven antecedents and the intercorrelations between antecedents. A total of 28 effects were calculated, utilizing 48 studies and 444 individual effect sizes, using 14,802 subjects. Using meta-analytically derived values, regression and relative weight analysis then determined each antecedent's relative utility. Furthermore, moderator analyses examined whether eight theoretically based moderators influenced the relationships between the antecedents and eWallet use intention.FindingsPrice value, hedonic motivation, facilitating conditions and social influence had the strongest relationships with the intention to use eWallets, accounting for virtually all the unique variance. The three weakest antecedents, however, still explained a large percentage of variance. No relationships were significantly moderated.Research limitations/implicationsDue to the lack of data in primary studies, some UTAUT moderators could not be analyzed. Also, common method variance may impact the findings because the primary studies used cross-sectional surveys.Practical implicationsThis study provides guidance regarding how companies can increase eWallet adoption rates, which have lagged in certain countries. These recommendations include specific techniques for tailoring messages and emphasizing features and benefits.Originality/valueTo the best of the authors’ knowledge, this is the first integrative meta-analysis conducted on eWallet use. Combining meta-analysis, regression and relative weight analysis, this study provides an integration of what is currently known about eWallet use intentions.